Efficacy and Safety of Qinghao Biejia Decoction in the Treatment of Systemic Lupus Erythematosus: A Systematic Review and Meta-Analysis - Li, Xiaobo; He, Zhouqing; Ru, Li; Yuan, Yueming; Yuan, Zheng; Chen, Pengfei; Xu, Zhiyong; Wang, Qi; Song, Jianping; Xu, Qin (Frontiers in Pharmacology, 2021)
Objective: This meta-analysis aimed to systematically assess the therapeutic efficacy and safety of Qinghao Biejia decoction combined with conventional chemical medicine in patients with systemic lupus erythematosus (SLE), and to provide reference for clinical medication. Methods: Multiple databases were retrieved by computer for randomized controlled trials (RCTs) of treating SLE with Qinghao Biejia decoction combining chemical medicine, from the establishment of the database to January 2021. Study screening, data collection, and quality assessment were performed independently by two reviewers. RevMan 5.4 and Stata 15.1 software were used for Meta-analysis. Results: Nine eligible studies, involving 655 SLE participants, were included. Meta-analysis showed that the additional use of Qinghao Biejia decoction superior to chemical medicine alone in people with SLE in improving the overall response rate (RR = 1.30, 95% CI [1.19, 1.41], P < 0.00001, heterogeneity P = 0.61, I2 = 0%), and can decrease SLE Disease Activity Index (SLEDAI) and TCM symptom scores, improve immunological indexes (C3, C4, IgG, IgA, IFN-γ, IL-4, Th1/Th2), reduce the occurrence of adverse events in treatment (P ≤ 0.05). Conclusion: Based on this meta-analysis, the additional use of Qinghao Biejia decoction has more advantages in the treatment of SLE than conventional chemical medication alone, which could enhance the efficacy and reduce adverse reactions, and is worthy of clinical promotion. However, more and higher quality RCTs are still need to confirm our findings.